Black Truffle Aqueous Extract Attenuates Oxidative Stress and Inflammation in STZ-Induced Hyperglycemic Rats via Nrf2 and NF-κB Pathways - Zhang, Tongze; Jayachandran, Muthukumaran; Ganesan, Kumar; Xu, Baojun (Frontiers in Pharmacology, 2018)
Background and purpose: Tuber melanosporum (black truffle) has been considered as a medicinal mushroom for a long time. T. melanosporum has the ability to attenuate oxidative stress and in turn diabetes mellitus (DM). DM has become an awfully common chronic unwellness, threatening people’s well-being. There are nearly 1 in 10 people in the world affected by diabetes. Oxidative stress plays a crucial role in vascular complications related to DM. Our study aimed to attain an effective treatment method to alleviate oxidative stress by scavenging free radicals and reducing inflammation, to display how truffle aqueous extract (TE) attenuates hyperglycemia Methods: Streptozotocin (STZ)-induced hyperglycemic rat model was accustomed to checking the hypoglycemic effect of black truffle by relating it with Nrf2 and NF-kB pathways. Varied biomarkers and inflammatory markers were analyzed. Results: Rats treated with TE showed reduced glucose levels, attenuated oxidative stress through regulation of SOD, CAT, VIT-E, and VIT-C. The gene expression of Nrf2 and NF-kB in rats treated with TE was increased to normal group level. The mRNA expression of inflammatory pathway genes and oxidative stress pathway genes in rats treated with TE was brought back normal. Similar results were achieved in the rats treated with standard drug, glibenclamide (GB). TE conjointly inhibits the state of inflammation within the tissues generally littered with the symptoms of hyperglycemia. Conclusion: The results of our study show the hypoglycemic impact of black truffle on STZ-induced hyperglycemia in rats via Nrf2 and NF-kB pathways, and both pathways have significant improvement that may support the hypoglycemic impact of truffle.